Sound discourse in strategies on collective memory in post-conflict periods: the case of “La Oruga” - Tamariz Bernal, Alfonso Antonio (2024)
This study analyzes the sound discourse in the podcast “La Oruga” as a strategy to construct and transmit the collective memory of the internal armed conflict in Peru (1980-2000). Using a qualitative approach, five representative episodes of the podcast were purposively sampled and analyzed by means of a content analysis form adapted to the sound format and the context of collective memory. The results reveal that the sound symbolism, the recreation of the testimonies and their centralization are, among others, powerful elements in the construction of a multidimensional narrative of the conflict that manages to give voice to historically marginalized perspectives, thus contributing to a more inclusive, deep and complex collective memory of the Peruvian internal armed conflict. It is concluded that sound discourse, through the podcast format, is currently a strategy under construction that in a post-conflict context allows a more empathetic and pluralistic approach to traumatic historical events, facilitating their understanding and aiming at reconciliation.